SOCIAL CRITICISM OF DANGDUT PANTURA - Siswo Harsono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
This research concerns with social criticism of Dangdut Pantura. The purpose of this research is to investigate a social criticism represented in video music of Dangdut Pantura. The objects of this research are “Sindiran”, “Sindiran 2”, “Sindiran 3”, and “Sindiran 4” video clips. This research uses critical theory, and textual and contextual methods. All video clips represent social criticism on social life related to elite politic and lower culture. It can be concluded that Dangdut Pantura represents social criticism on sosial and political life in the society.Keywords: Dangdut Pantura, social criticism, elite society.